Pengaruh Emosi Positif Terhadap Hasil Pengobatan Penyakit Rheumatoid Arthritis - Luthfiah Mawar; M. Agung Rahmadi; Helsa Nasution; Ika Sandra Dewi; Milna Sari (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
This study evaluates the impact of positive emotions on rheumatoid arthritis (RA) treatment outcomes through a meta-analysis of 47 studies (2015-2024) involving 12,384 patients. The primary findings reveal a significant positive correlation between positive emotions and improved RA treatment outcomes (r = 0.42, p < 0.001), with the strongest effects observed in enhanced quality of life (r = 0.51) and physical function (r = 0.45). Patients exhibiting high positive emotions demonstrated greater reductions in pain (d = 0.38), decreased inflammation (d = 0.29), and improved physical function (d = 0.45) compared to control groups. Moreover, moderator analyses uncovered stronger effects among elderly patients (? = 0.012, p = 0.025) and those with longer RA duration (? = 0.018, p = 0.009). Finally, mediational analyses indicated that positive emotions contributed to improved treatment adherence (indirect effect = 0.09, 95% CI [0.05, 0.13]) and increased physical activity (indirect effect = 0.07, 95% CI [0.03, 0.11]) in RA patients. These findings extend Fredrickson's (2001) Broaden-and-Build theory and support Keefe et al.'s (2002) biopsychosocial model. Compared to meta-analyses by Brosseau et al. (2018) and Zhou et al. (2020), this study provides more comprehensive evidence on the role of positive emotions in various RA treatment outcomes. The novelty of this research lies in the analysis of previously unexplored mediating and moderating mechanisms, as well as a comparison of effectiveness with pharmacological interventions (SMD = 0.18, 95% CI [-0.05, 0.41], p = 0.124). These results support the integration of positive emotion-based interventions in RA management and expand upon Strand et al.'s (2019) findings on patient expectations in RA treatment.